Divergent population dynamics: The case of the inner city of Riga - Balode, Sindija; Krišjāne, Zaiga (Rozwój Regionalny i Polityka Regionalna, 2024)
Population dynamics shape the spatial landscape of Europe. Although broadly studied, both suburban sprawl and inner-city reurbanisation have often been treated in isolation. Furthermore, these processes manifest distinctively across different local contexts. This research aimed to explore the population dynamics in the inner city of Riga from 2011 to 2021, contrasting them with the bordering municipalities of Riga, and to analyze how these dynamics align with the urban development model. Covering 58 neighborhoods and 7 bordering municipalities of Riga, the analysis revealed a shift in the trajectory of inner-city population dynamics during the latter half of the decade, which was finally characterized by growth. However, suburbanisation continued to outpace reurbanisation, indicating the coexistence of multiple urban development model stages.